Extrovert Students’ Communication Effectiveness in Solving Mathematical Problems - Anna Nur Fadillah; Abdur Rahman As’ari; Makbul Muksar (Jurnal Pendidikan Sains, 2020)
Abstract:  The purpose of this article is to describe the effectiveness of communication of extroverted students in mathematical problem-solving. The trial subjects were two high school students in class XII who had extroverted personalities. Measurement of the level of similarity in understanding or effectiveness of communication seen based on the results of interviews with two research subjects. Based on observations during the problem-solving process and analysis of communication effectiveness, it is found that students' mathematical communication in solving problems is very effectiveAbstrak: Tujuan dari artikel ini adalah untuk mendeskripsikan efektivitas komunikasi siswa berkepribadian ekstrovert dalam pemecahan masalah matematis. Subyek uji coba adalah dua siswa kelas XII SMA yang memiliki kepribadian ekstrovert. Pengukuran tingkat kesamaan pemahaman atau efektivitas komunikasi dilihat berdasarkan hasil wawancara dengan dua subjek penelitian. Berdasarkan hasil pengamatan selama proses pemecahan masalah dan analisis efektivitas komunikasi didapatkan bahwa komunikasi matematis siswa dalam memecahkan masalah sangat efektif.